PSYCHOTROPIC MEDICATIONS: AN UPDATE FOR SCHOOL PSYCHOLOGISTS. Issue 6 (14th May 2013) - Rappaport, Nancy; Kulick, Deborah; Phelps, LeAdelle
<x xml:space="preserve">Abstract</x> This article provides an overview of medications used frequently in the treatment of pediatric depression, anxiety, and bipolar disorder. The need for a collaborative relationship between the prescribing physician, school personnel, and the family is outlined. School psychologists can play crucial roles by providing the physician with information at the time of referral, developing school‐based psychosocial interventions that augment pharmacological treatment, completing periodic evaluations to assist in symptom monitoring, and alerting the family and physician to any adverse side effects.